The status of diabetes control and complications in a single tertiary institution in Kuala Lumpur - Omar , Ahmad Marzuki; Shahar, Mohammad Arif; Wan Seman, Wan Juani; M., Azura Dina; Rajoo, Subashini; Chew, Peng Ooi; Huai, Heng Loh; Omar, Mohd Rahman; A Wahab, Norasyikin; Mustafa, Norlaila; Sukor, Norlela; Kamaruddin, Nor Azmi (ASEAN Federation of Endocrine Societies, 2015)
Background: The prevalence of type 2 diabetes mellitus (T2DM) in Malaysia continues to increase over the last two decades. Even with the availability of resources and expertise, the metabolic control and rate of complications remained unsatisfactory. Objectives: The study was conducted to evaluate the status of diabetic control and rates of complications in a dedicated diabetic clinic in a tertiary teaching hospital. Material and Methods: This was an observational, non-interventional, cross-sectional study conducted among T2DM patients attending two prespecified clinic days, fulfilling the inclusion and exclusion criteria. Results: Out of 103 consecutive subjects, there were 35 (34.0%) males and 68 (66.0%) females, with a mean age of 60.5±10.7 years. By ethnicity, 49 (47.6%) were Malays, 35 (34.0%) Chinese, 18 (17.5%) Indians and 1 (1.0%) of other ethnicity. Mean body mass index (BMI) was 29.1±6.9 kg/m², with majority of them (83.3%) were overweight or obese (BMI ≥23 kg/m²). Mean duration of diabetes was 15.2±8.8 years with two-third (66.0%) who had diabetes for more than 10 years. Mean HbA1c was 8.2±1.8% with only 20.4% of the subjects achieving the target level of <6.5%, while 31.1% of them achieved ADA target of <7%. Mean fasting plasma glucose was 8.0±4.1 mmol/L with 37.4% of them achieved the target level of ≤6.1 mmol/L. Three-quarter (75.7%) of subjects were on metformin while insulin was used in 71.8% of them. Only 27.5% achieved blood pressure of ≤130/80 mmHg although 84.5% of them were on antihypertensive agents, with over two-third (68.4%) were on either ACE inhibitors or angiotensin receptor blockers. Up to 67.3% of subjects achieved LDL-cholesterol levels of ≤2.6 mmol/L, with 81.2% had HDL-cholesterol levels of ≥1.1 mmol/L and 64.4% had triglycerides of ≤1.7 mmol/L. Statins were used by 89.6% of the subjects. The rates of diabetic complications were microalbuminuria (37.9%), cataract (35.9%), peripheral neuropathy (33.0%), myocardial infarction (6.8%) and cerebrovascular accident (6.8%). Conclusions: Majority of subjects were overweight or obese with long-standing diabetes. Overall, the glycaemic, blood pressure and lipids levels were not satisfactorily controlled, hence the high rates of complications.